Unilateral absence of pulmonary artery: a radiographically occult cause of life-threatening hemoptysis - Agrawal, Juhi; Reghunath, Anjuna; Paruthi, Charu; Mittal, Mahesh K.; Sinha, Mukul; Thukral, Brij B. (International Journal of Research in Medical Sciences, 2020)
Unilateral absence or agenesis of pulmonary artery (UAPA) is a rare congenital abnormality with an estimated prevelance of 1 in 2,00,000 adults. The entity occurs commonly in association with other congenital heart diseases like septal defects or patent ductus arteriosus. The condition usually runs a benign clinical course with patients usually presenting clinically in adulthood with history of recurrent respiratory tract infections. Two such patients presented with recurrent respiratory tract infections, breathlessness and hemoptysis. The chest radiograph of first patient was reported as normal in the referring hospital, while that of second patient showed volume loss in left lung. CT Pulmonary Angiography (CTPA) was then performed which demonstrated the absence of right and left pulmonary arteries respectively in the first and second patients. Pulmonary artery branches were reformed distally by multiple collaterals arising from systemic arteries. The entire spectrum, including embryology, imaging features and management of UAPA are discussed. UAPA remains a potential cause for life-threatening hemoptysis, due to extensive collateralization associated with the condition. It is important for radiologists to be aware of this uncommon entity in order to suspect it on a routine chest radiograph, diagnose it and map associated collaterals on CTPA and also embolize the bleeding collaterals.